Decoding the Essence of Storytelling: A Research Study - Raz, Abdul Rauf (sourcecoder, 2024)
Dastan, derived from Persian and Urdu, embodies the art of storytelling in the form of epic tales, myths, and legends. These narratives, often passed down through generations, serve as repositories of cultural identity, transmitting values, beliefs, and traditions. The essence of Dastan lies not only in the plotlines but also in the intricate interweaving of emotions, moral lessons, and the collective memory of a community. At its core, legends ( Dastan) is a dynamic genre that adapts to the socio-cultural context, reflecting the aspirations, fears, and wisdom of diverse societies. The stories, whether mythical or historical, often feature heroic figures grappling with challenges, moral dilemmas, and cosmic forces. This paper explores the archetypal elements present in Dastan, highlighting the universal themes that resonate across cultures.